Reconstruction in early squamous cell carcinoma of the oral cavity - do free flaps improve oncological outcome? - Moratin, Julius; Zittel, Sven; Ristow, Oliver; Hoffmann, Jürgen; Freier, Kolja; Horn, Dominik (Journal of stomatology, oral and maxillofacial surgery, 2025)
Background - Oral squamous cell carcinoma (OSCC) ranks on position 14 in global cancer analysis and makes up to 38 % of all head and neck squamous cell carcinomas. While surgery is accepted as first-line treatment of early tumors, the reconstructive approach is not standardized. Therefore, we evaluated the concept of ablative tumor removal and microvascular reconstruction in terms of oncological safety and surgical morbidity for early OSCCs. - Methods - 262 patients received ablative tumor surgery with neck dissection together with microvascular reconstruction between 2010 and 2020. General clinical data was analyzed descriptively with regard to surgery time, duration of tracheotomy and hospitalization. - Results - Estimated 5-year overall and progression-free survival was 85 % and 77 % respectively with no significant difference between stage I or II cancer patients. Tracheotomy was performed in 131 patients (50 %). 19 patients (7.3 %) were temporarily dependent to a gastric feeding tube. Flap loss occurred in 9 patients (3.4 %). - Discussion - In a standardized setting, mean surgery time could be reduced constantly. We propose consistent tumor ablation, combined with elective neck dissection and microvascular reconstruction in early oral squamous cell carcinoma. The presented concept leads to excellent oncological and functional results with acceptable morbidity and short surgery times.
Online verfügbar: 16. Oktober 2024, Artikelversion: 5. Dezember 2024
Gesehen am 05.03.2025